The Effect of Gender and Zigzag Run Game on Children's Gross Motor Development in Kuncup Mekar Kindergarten Alahan Panjang - Livia, Resvi; Rakimahwati, Rakimahwati; Yaswinda, Yaswinda; Nurhafizah, Nurhafizah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to analyze the effect of the Zig-Zag Run game and gender on the development of children's gross motor skills at the Kuncup Mekar Alahan Panjang Kindergarten. This study uses a quantitative approach with an experimental type. The objects of the study were children aged 5-6 years at the Kuncup Mekar Kindergarten, and the study was conducted from August 2023 to April 2024. Data were collected through observation using observation sheets tested for validity and reliability. The data collection technique used a performance test involving the Zig-Zag Run Games activity. Data analysis was carried out using a t-test to compare the difference in average values between the control and experimental groups and normality and homogeneity tests. The results showed that the Zig-Zag Run game significantly increased children's gross motor skills by 0.001, and gender did not affect this development. The simultaneous test of both gave an effect of 0.949. It is proven that the Zig-Zag Run game is effective in improving children's gross motor skills and is recommended to be implemented in kindergartens.